Entre textos, entre linhas: a polissemia no livro didático acionada pelo gênero tirinha - Brito, Nilcemere D’Ark da Silva (2018)
In recent decades, one can observe the development of numerous grammatical studies, intended for the study of the syntax of the language, however, are still a few jobs that are semantic analysis of linguistic phenomena. Therefore, this research has two main objectives: the first is it to investigate how students in the sixth grade of elementary school to a public school in the town of Boqueirão, Paraíba, treat the Semantic phenomenon of polysemy when found in texts of the genre comics and the second is to analyze how the textbook of Portuguese – Teláris Project addresses in your content the phenomenon of polysemy. Our investigation arises from the problematization in understanding how far the student of the initial series of elementary school II, in particular, the sixth grade, can identify and recognize the presence of polysemy through textual/discursive genre comics. In this way, we seek to accomplish a job which, through reading and critical interpretation and conscious contributes to a knowledge-oriented learning that contributes to the formation of critical citizens and active in society. The search is by Semantic Example Norther. We bring, therefore, to the scene, theoretical discussions of authors as Kock and Elias (2006), discussing the reading under the discursive paradigm; Bakhtin (2000) and Marcuschi (2008) depends on the discussion of textual/discursive genres; Nicolau (2007) as regards the genre comics; Chierchia (2008) and Pietroforte and Lopes (2007) and Guimarães (2002) discussing Semantics, lexicon and polysemy; Dionísio and Bezerra (2005) with regard to the textbook; Lopes-Rossi (2002) deals with the following activities, among others. Our hypothesis is the possibility to promote critical reading, conscious and at the same time, streamline, participatory and effective literacy. We consider important the adoption of comics as corpus of our work, for being a dynamic text that brings, through verbal and non-verbal language, critical, humorous content, social and cultural rights, and inviting to our audience – children and adolescents – which often do not have the habit and not demonstrate interest in the practice of reading, which is also the subject of our research. In this context, we articulate a reading project, by means of a sequence of activities that includes texts and questions using the comic strip genre to explore the semantic phenomenon of polysemy.